Cost‐Effectiveness of New Direct‐Acting Antivirals to Prevent Post–Liver Transplant Recurrent Hepatitis. Issue 7 (July 2015) - Cortesi, P. A.; Mantovani, L. G.; Ciaccio, A.; Rota, M.; Mazzarelli, C.; Cesana, G.; Strazzabosco, M.; Belli, L. S.
<x xml:space="preserve">Abstract</x> Preliminary studies on HCV‐cirrhotics listed for transplant suggest that sofosbuvir in combination with ribavirin is very effective in promoting viral clearance and preventing disease recurrence. Unfortunately, the high cost of such treatment (€46 500 per 12 weeks of treatment) makes its cost‐effectiveness questionable. A semi‐Markov model was developed to assess the cost‐effectiveness of sofosbuvir/ribavirin treatment in cirrhotic patients without HCC (HCV‐CIRRH) and with HCC (HCV‐HCC) listed for transplant. In the base‐case analysis, the incremental cost‐effectiveness ratio for 24 weeks of sofosbuvir/ribavirin was €44 875 per quality‐adjusted life‐year gained in HCV‐CIRRH and €60 380 in HCV‐HCC patients. Both results were above the willingness to pay threshold of €37 000 per quality‐adjusted life‐year. Our data also show that in order to remain cost‐effective (with a 24‐week treatment), any novel interferon‐free treatment endowed with ideal efficacy should cost less than €67 224 or €95 712 in HCV‐cirrhotics with and without HCC, respectively. The results shows that sofosbuvir/ribavirin therapy, given to patients listed for transplant, is not cost‐effective at current prices despite being very effective, and new, more effective treatments will have little economic margins to remain cost‐effective. New interferon‐free combinations have the potential to revolutionize the treatment and prognosis of HCV‐positive patients listed for transplant; however, without sustainable prices, this revolution is unlikely to happen.